Prevalência e Fatores de Risco Associados à Colonização por Candida spp. em Lesões Da Mucosa Bucal - Feletti, Mariana Pires (2024)
The present study aimed to evaluate the prevalence of Candida spp. in lesions that affect the oral mucosa, assess the distribution of Candida species present, and analyze the risk factors associated with this relationship. A cross-sectional study was conducted in which patients with lesions on the oral mucosa underwent swab collection to investigate Candida spp. The first collection was carried out in the lesion area, and a second in the mucosa region without apparent lesion. Patient samples were plated on CHROMagar Candida™, and colony-forming unit counts were performed to determine fungal load. Biochemical, morphological, and mass spectrometry tests were carried out to identify the species, followed by in vitro sensitivity tests to antifungals. The data collected indicated a prevalence of 40% of Candida spp. associated with oral lesions in x patients evaluated. Among the most commonly found species, C. albicans (62.5%), C. glabrata (10.5%), C. parapsilosis (7.5%), and C. tropicalis (7.5%) stood out. It was observed that the presence of the lesion was a factor that influenced the occurrence of Candida spp., with a more significant occurrence of this microorganism in areas of altered mucosa. Furthermore, Candida spp. it was more prevalent in elderly, female, and diabetic patients. No association was identified between Candida spp. and lesions in the oral mucosa with hyposalivation, history of smoking, and alcohol consumption. Of the 37 samples submitted to antifungal susceptibility testing, all have a resistance profile to Nystatin. Based on the data from this study, it is concluded that lesions in the oral mucosa represent a risk factor for colonization by Candida spp. Although most species identified are C. albicans, nonalbicans species were isolated in the oral cavity of patients, emphasizing C. parapsilosis. Understanding the relationship between species and lesions in the oral mucosa is crucial for safer and more effective patient clinical management.